Risk factors for postoperative late deterioration in patients with spinal dural arteriovenous fistulas - Ge, Yuanhong; Lai, Qingjia; Guo, Wei; Xu, Xuejun (Frontiers in Neurology, 2024)
Approximately 86% of patients with spinal dural arteriovenous fistulas (SDVAFs) exhibit clinical improvement after surgery. However, 12%-55.8% of these patients experience late deterioration (LD) after an initial period of improvement. The risk factors for LD remain unclear. The aim of this study was to explore the risk factors for LD in SDVAF patients. The clinical data of patients who were admitted to two tertiary hospitals between June 2014 and May 2022 were reviewed. Patients were divided into two groups: the LD group and the no LD group. The severity of neurological dysfunction (NDF) was evaluated using the Modified Aminoff and Logue Scale. Univariable and multivariable Cox regression analyses were performed. A total of 105 eligible patients were enrolled, with a mean age of 57.55 ± 9.42 years. The LD group comprised 37 individuals, while the no LD group consisted of 68 individuals. According to the univariable analysis, preoperative NDF severity and treatment strategy were associated with the risk of LD. According to the multivariable analysis, patients who underwent microsurgery (MS) had a lower risk of LD than did those who underwent endovascular treatment (EVT) (HR 0.197, 95% CI 0.085-0.457), and patients with severe NDF had a higher risk of LD than did those with mild NDF (HR 3.604,, whereas the risk of LD in patients with moderate NDF was similar to that of patients with mild NDF (HR 1.352, 95% CI 0.519-3.524). Finally, we concluded that EVT and severe preoperative NDF are independent risk factors for LD.